2015
DOI: 10.1016/j.ejbas.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pathogenic bacteria on reliability of CK-19, CK-20 and UPII as bladder cancer genetic markers: A molecular biology study

Abstract: a b s t r a c t Objectives: To evaluate the effect of the presence of pathogenic bacteria in urine on three bladder cancer genetic markers (Cytokeratin 19, Cytokeratin 20 and Uroplakin II mRNA), and to evaluate the reliability of each urine marker separately. Methods: Voided urine samples from 20 bladder cancer patients, 15 patients with urinary tract infection patients and 10 healthy volunteers were collected. Isolation and identification of bacteria was performed followed by determination of antimicrobial su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Reduction of epithelial markers have been highlighted in our previous research among infected bladder cancer patients less than those without infection 18 . This finding goes hand in hand with study performed by Leone et al 20 as it was reported K. pneumoniae ability to promote EMT-like programs in airway epithelial cells through direct interaction.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Reduction of epithelial markers have been highlighted in our previous research among infected bladder cancer patients less than those without infection 18 . This finding goes hand in hand with study performed by Leone et al 20 as it was reported K. pneumoniae ability to promote EMT-like programs in airway epithelial cells through direct interaction.…”
Section: Discussionmentioning
confidence: 60%
“…This study reveals that bacterial infection triggers EMT features such as reduction of epithelial marker (CK19) and upregulation of mesenchymal marker (vimentin). Reduction of epithelial markers have been highlighted in our previous research among infected bladder cancer patients less than those without infection 18 . This finding goes hand in hand with study performed by Leone et al 20 as it was reported K .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…CK19 is one of these tumor markers as a result of its expression in the uroepithelial cells. CYFRA 21‐1 has been applied as a prognostic and diagnostic tumor marker for middle cell neoplasm of the urothelium (El Shobaky, Abbas, Raouf, Zakaria, & Ali‐El‐Dein, ).…”
Section: Ck19 In Various Cancer Cellsmentioning
confidence: 99%
“…The device was designed to fit a 100-mm dish, filled with a thin film of sterile deionized water and stored in a humidified chamber to minimize the evaporation of long-term cultures (Berthier et al 2008). Since UTI caused by UPEC infection is a contributing factor to the development of bladder cancer, and UPEC is similarly associated with bladder cancer (Chagneau et al 2020;El Shobaky et al 2015), we utilized bladder cancer cells (UMUC-3) and the UPEC strain (UTI89) in this proof-of-concept study. The cells were uniformly suspended in the growth medium and seeded into each microchannel.…”
Section: Development Of the Microfluidic Platform To Analyze The Effe...mentioning
confidence: 99%